Helium accumulation characteristics and main controlling factors of helium depletion in Daniudi Gas Field, Ordos Basin - Jie WANG; Chuan AN; Liangbang MA; Haijian JIANG; Wei ZHANG; Cheng TAO; Fubin WANG; Qingwei DONG (Shiyou shiyan dizhi)
A certain amount of helium is found in the natural gas of both the Dongsheng and Daniudi gas fields in the Hangjinqi area of the Ordos Basin. However, the average helium content in the Daniudi Gas Field is only about one-fourth of that in the Dongsheng Gas Field. Given the similar basement geology and tectonic background of the basin, it is necessary to investigate the factors leading to this significant difference. A systematic analysis of the geochemical characteristics of associated helium in natural gas and the key factors controlling helium accumulation was conducted. The results revealed that the helium content in the Paleozoic natural gas of the Daniudi Gas Field ranged from 0.000 1% to 0.15%, classifying it as a low- to medium-helium gas field. Helium content in the Upper Paleozoic was relatively higher, and vertically, it gradually increased from the lower to the upper layers, showing relative enrichment in shallower layers. The helium in the Paleozoic source rocks of the Daniudi Gas Field was typical crust-source helium, mainly derived from the Archean-middle Paleoproterozoic metamorphic rock-granite series in the basin basement. The contribution of helium generated by potential helium source rocks in the Upper Paleozoic was minimal. By comparing the geological conditions and accumulation characteristics of the Upper Paleozoic between the Daniudi and Dongsheng gas fields, it was found that the basement helium source rocks in both gas fields were similar in rock type, mineral composition, thickness, and uranium (U) and thorium (Th) contents, suggesting that the differences in source rock were not responsible for the significant difference in helium content. In the Daniudi area, only one second-level deep fault was developed in the basement of the Daniudi area, and its activity during the Yanshanian-Himalayan period was relatively weak, resulting in limited activity of secondary faults. This led to a lack of effective channels for helium to migrate upward from the basement helium source rocks, as well as vertical transport and lateral adjustment. Due to the mismatch in spatiotemporal configuration of key accumulation factors for helium and conventional gas, helium entered the Paleozoic gas reservoirs in Daniudi only by diffusion, resulting in low helium content. Therefore, the main factors contributing to helium depletion in the Daniudi Gas Field are the underdevelopment and weak activity of deep faults and secondary faults in the basement, the mismatch between helium and conventional gas accumulation conditions, the lack of an effective transport system, and the reliance on concentration-driven diffusion for helium migration.